Promoting foreign investment in tourism (UN New YorkUS, 2010)
Presents a case for investment promotion agencies (IPA) to consider which tourism sectors and subsectors within their territory could generate internationally mobile projects, which of these should be targetted for promotion and to develop specific criteria. Develops and implements contact strategies for targetted firms and finally evaluates the results of its efforts.
Keywords: TOURISM